Success factors for corporate innovation: the core of business "value creation" - Amthor, Nicolas (2022)
Understanding the success factors for corporate innovation is essential for businesses to grow. This research focused on how the external (user)and internal (employee, process) side scan foster innovation. The results showed that including the user in the innovation process increases their willingness to pay. On the internal side, 15 challenges were uncovered for Test & Learn process adoption in CPG corporates. Additionally, innovative work behaviors are promoted by employee motivation, both intrinsic and extrinsic. Incentives are important, but companies should rather ensure employees enjoy their tasks and have the freedom to make mistakes when innovating in the workplace.